HINDU DITENGAH KLAIM PEMBENARAN KEYAKINAN - Putu Dana Yasa (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
Lately there have been so many religious problems that have arisen both in the real world and in cyberspace. Various justification claims appear in an effort to maintain the self-esteem of one's beliefs, these justification claims become so dangerous because one can easily judge other people's beliefs and assume that what they believe is the only truth while other beliefs are wrong. This is what makes it interesting to carry out scientific studies in an effort to offer solutions to religious disputes that seem to be an eternal war. All religions without exception Hinduism, of course, have offered various concepts of harmony as a human guide in carrying out life regardless of religious background, ethnicity, customs and other things. So far, claims of justification have arisen from individuals who do not fully understand their religious teachings, but already feel they know everything themselves. Apart from that, not a few also use religion as a political vehicle to defeat political opponents, because by using very sensitive religious issues it becomes the main weapon to gain the sympathy of the people who are psychologically very motivated when talking about religion.